Pelatihan bagi Calon Guru SD Menyusun Teks Wacana Artefak bermuatan Literasi Budaya Pola Hidup Sehat - Dina Mardiana; Simpun Simpun; Hendrowanto Nibel; Orbit Thomas; Missesa Missesa; Fahrul Razzi; Iwan Fauzi (IKIP PGRI Bojonegoro, 2025)
ABSTRACT The PDPPM program is one of the schemes in community service activities at the Faculty of Teacher Training and Education, the University of Palangka Raya (FKIP UPR). This activity program was carried out by the lecturer team from the faculty to provide training to 36 prospective elementary school teachers in the PGSD Study Program, FKIP UPR on the utilization of local cultural artifacts as cultural literacy of healthy lifestyles in the content of Indonesian language learning materials based on text genres in elementary schools. From the results of the evaluation given to the activities and performance of partners as training participants, improvements were obtained that included: (1) knowledge and skills about healthy lifestyles applied in the results of the analysis of local cultural artifacts, (2) knowledge and skills of healthy lifestyle concepts packaged in a local cultural artifact discourse text centered on the socio-cultural background of students in the class they teach, (3) knowledge and skills in using participatory learning methods by emphasizing independent learning through providing concrete examples of the content of artifact discourse material as cultural literacy of healthy lifestyles, and (4) knowledge and skills in using local sources as material for artifact discourse material based on text genres written to suit the characteristics of the artifacts used. This is indicated by the average class score obtained from the evaluation results of training participants, namely 87.5 with 100% completion and categorized as very good.Keywords: artifact discourse, cultural literacy, healthy lifestyle, language learning, elementary school ABSTRAK Program PDPPM merupakan salah satu skim dalam kegiatan pengabdian kepada masyarakat di Fakultas Keguruan dan Ilmu Pendidikan Universitas Palangka Raya (FKIP UPR). Kegiatan ini dilaksanakan oleh Tim Dosen dari FKIP UPR guna memberikan pelatihan kepada 36 orang calon guru SD di Prodi PGSD FKIP UPR tentang pemanfataan artefak budaya lokal sebagai literasi budaya pola hidup sehat dalam muatan materi pembelajaran bahasa Indonesia berbasis genre teks di sekolah dasar. Dari hasil evaluasi yang diberikan terhadap aktivitas dan kinerja mitra sebagai peserta pelatihan diperoleh peningkatan yang mencakupi: (1) pengetahuan dan keterampilan tentang pola hidup sehat yang diaplikasikan dalam hasil analisis artefak budaya lokal, (2) pengetahuan dan keterampilan konsep pola hidup sehat yang dikemas dalam sebuah teks wacana artefak budaya lokal yang berpusat pada latar belakang sosial budaya peserta didik di kelas yang diampunya, (3) pengetahuan dan keterampilan menggunakan metode pembelajaran yang partisipatif dengan menggunakan penekanan pada belajar mandiri melalui pemberian contoh yang kongret dari muatan materi wacana artefak sebagai literasi budaya pola hidup sehat, dan (4) pengetahuan dan keterampilan tentang penggunaan sumber lokal sebagai bahan materi wacana artefak berbasis genre teks yang ditulis menyesuaikan dengan karakteristik artefak yang digunakan. Hal tersebut ditunjukkan dengan perolehan nilai rata-rata kelas dari hasil evaluasi terhadap peserta pelatihan, yaitu 87,5 dengan 100% tuntas dan berkategori sangat baik.Kata Kunci: wacana artefak, literasi budaya, pola hidup sehat, pembelajaran bahasa, sekolah dasar